Pengaruh Motivasi Belajar dan Teman Sebaya Terhadap Minat Belajar Pendidikan Pancasila dan Kewarganegaraan - Rika Nur Hidayah; Bambang Sumardjoko; Arif Subowo (Publikasi Indonesia, 2025)
Interest has a big influence in the learning process, without interest, students will not be able to learn well. The purpose of this research was to determine the effect of learning motivation and peers on the interest in learning Pancasila and Civic Education of students at State Junior High Schools in Ngrampal District. The method used in this study is a quantitative method with a correlational research type. The population in this study consisted of 1,265 students from two schools, namely State Junior High School 1 Ngrampal and State Junior High School 2 Ngrampal, with a sample of 127 students. The results of this study are that learning motivation influences learning interest with a significance of 0.000 <0.05. Peers influence learning interest with a significance of 0.003 <0.05. Learning motivation and peers influence students' learning interest with a significance of 0.000 <0.05, and an influence of 51,6% in increasing students' learning interest, so that if students have strong learning motivation and receive peer support, students' learning interest will be high.